RNA binding protein HuD regulates fatty acid oxidation in pancreatic β-cells by modulating long-chain acyl-CoA dehydrogenase expression - Jiyoon Seo; Seungyeon Ryu; Wei Zhang; Eun Kyung Lee; Seung Min Jeong (Animal Cells and Systems)
RNA binding proteins (RBPs) play crucial roles in the post-transcriptional regulation of metabolic pathways. Although the RBP HuD has been extensively studied in pancreatic β-cells, its role in cellular metabolism remains poorly understood. In this study, we uncover a novel function of HuD in regulating fatty acid oxidation (FAO) in mouse insulinoma βTC6 cells. Through genetic knockdown and overexpression approaches, we demonstrate that HuD modulates the expression of long-chain acyl-CoA dehydrogenase (LCAD), a key enzyme in FAO, by binding to the 3′-untranslated region of its mRNA. Loss of HuD impaired FAO, leading to lipid droplet accumulation, elevated reactive oxygen species production, and increased lipotoxicity under lipid-stress conditions. These findings reveal a previously unrecognized role for HuD in maintaining fatty acid homeostasis and suggest that the HuD-LCAD regulatory axis may represent a promising therapeutic target for preserving β-cell integrity and function.